A study on chronicity and treatment response of functional abdominal pain in 5 to 15 years of children, in relation to size and location of primary mesenteric lymphadenitis in a tertiary care centre - Dr. Sudhanshu Kumar Das; Monalisa Subudhi (Pediatric Review: International Journal of Pediatric Research, 2020)
Introduction: Functional abdominal pain (FAP) is one of the most common childhood complaints ,an intermittent (recurrent abdominal pain or RAP) or continuous in nature, which cannot be explained by any visible or detectable abnormality, after a thorough physical examination and appropriate laboratory testing .It has negative effects on the child’s physical and psychological state and interfere their daily activities. The present study aimed to find out the chronicity and treatment response of functional abdominal pain in relation to size and site of location of in primary mesenteric lymphadenitis.Methodology: A prospective study was done on 156 patients, aged 5 to15 years, in the department of paediatric of GVPMC, Visakhapatnam, AP, a tertiary care hospital, from September 2017 to March 2019. Patient’s demographic profile, clinical features, physical examination and systemic examination were recorded. All the relevant investigations were done in all the patients. For the purpose of the study, all cases were categorised into four group, according to their site of pain. The presence of enlarged mesenteric lymph nodes, their location, size (transverse and anteroposterior dimensions) and other significant findings were recorded. Mesenteric lymphadenopathy was labeled significant using a short axis diameter of >5 mm in short axis diameter. Final diagnosis was established, and patients were followed in OPD.Result: Majority of children presented with abdominal pain, under 5 to 10 years age were female 38(51.35%) and 52 (63.41%) were male under 11 to 15 years. Most common abdominal site of Mesenteric lymph node enlargement was Periumbilical site followed by Right Iliac Fossa. According to the site of pain, Majority of the cases were under group I , 54 ( 34.61%) and group III, 42 (26.92%).In four groups , all relieved cases had lymph node of size 5mm to 8 mm ,except group III 16 (10.25%)cases and all persistent cases, lymph node size more than 8mm, except group II 20 (12.82%).Conclusion: Good approach can be obtained to these cases early and follow up regularly to, modify their painful early school life and assure the parents about the benign nature of the disease.